Digitizing the Canvas: Enhancing Early Childhood Fine Motor Skills through Touchscreen Finger Painting - Siti Mualifah; Aip Syarifudin; Abdul Muiz Rouf (Qualitative and Quantitative Research Center, 2026)
While empirical debates persist regarding the developmental impacts of screen time on early childhood, the pedagogical potential of touchscreen interfaces as positive motor stimulators remains under-explored. This study investigated the optimization of early childhood fine motor skills including finger flexibility, hand-eye coordination, and movement control through a structured touchscreen finger-painting intervention. Adopting a two-cycle action research framework, the intervention was deployed among 20 children aged 4 to 5 years. Data were gathered using a triangulated approach comprising systematic observation, practitioner interviews, and artifact documentation. Quantitative analysis revealed a significant developmental shift, where the percentage of children reaching high-level mastery of Developing as Expected and Very Well Developed increased from 65% in Cycle I to 80% in Cycle II. Beyond statistical gains, the qualitative insights demonstrated that the interactive haptic and visual feedback of the touchscreen interface significantly enhanced spatial control and visual-motor coordination. The primary contribution of this study lies in redefining digital interaction, demonstrating that touchscreen finger painting serves as an active pedagogical scaffolding tool rather than a medium for passive consumption.